Tax support evaluation for R&D activities of companies - Cernikova, Martina; Hyblerova, Sarka (Technological and Economic Development of Economy, 2021)
The article evaluates the impact of tax support for R&D on the volume of R&D outputs generated by companies. The number of patent applications was chosen as the R&D metric for business output. Both linear dependence using linear regression and non-linear dependence using decision trees were used within the research. The significance of indirect support in the context of other sources of funding R&D activities of companies was primarily assessed. The dependence of the number of patent applications on individual sources of financing of the Business Enterprise Expenditure on R&D was examined. Even after scaling variables, the research in the period under review confirmed the strongest dependence between the number of patent applications and the financial resources provided by the Business enterprise sector for all countries surveyed. Subsequently, the model reduced by the impact of Business enterprise sector resources was created. Of the three remaining variables considered, the analysis showed the strongest dependence of the number of patent applications on the amount of indirect support. The research points to the fact that impact of tax support on the volume of relevant R&D outputs is relatively significant.